2022
DOI: 10.3390/en15103636
|View full text |Cite
|
Sign up to set email alerts
|

A Combination Method of Liquid Hot Water and Phosphotungstic Acid Pretreatment for Improving the Enzymatic Saccharification Efficiency of Rice Straw

Abstract: Chemical pretreatment can significantly improve the enzymatic hydrolysis efficiency of lignocellulosic biomass, thereby improving the yield of sugar materials for the production of cellulosic ethanol, but commonly used acid–base catalysts are difficult to recover and reuse. In this work, a combination method of liquid hot water (LHW) and phosphotungstic acid (PTA) pretreatment was performed to improve the saccharification efficiency of rice straw, and we attempted to evaluate the reuse effect of PTA catalysts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The crystallinity index of pretreated bagasse was observed due to the elimination of the amorphous structure of hemicellulose and lignin; nevertheless, the crystalline structure of cellulose was relatively unaffected. Previously, increases in lignocellulose crystallinity were observed in various lignocelluloses pretreated with LHW, for instance, rice straw pretreated with LHW 25 and other pretreatment methods, e.g., dilute acid pretreatment 26 and alkaline pretreatment 27 . On the other hand, certain pretreatment techniques, such as ionic liquids, have been reported to cause complete destruction of the crystalline cellulose structure 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity index of pretreated bagasse was observed due to the elimination of the amorphous structure of hemicellulose and lignin; nevertheless, the crystalline structure of cellulose was relatively unaffected. Previously, increases in lignocellulose crystallinity were observed in various lignocelluloses pretreated with LHW, for instance, rice straw pretreated with LHW 25 and other pretreatment methods, e.g., dilute acid pretreatment 26 and alkaline pretreatment 27 . On the other hand, certain pretreatment techniques, such as ionic liquids, have been reported to cause complete destruction of the crystalline cellulose structure 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The increased crystallinity index of the pretreated bagasse was caused by the elimination of the amorphous hemicellulose and lignin structures; nevertheless, the crystalline structure of cellulose was relatively unaffected. Previous studies have found increased crystallinity indexes in various lignocelluloses pretreated with LHW, for example, rice straw pretreated with LHW, as well as other pretreatment methods such as dilute acid and alkaline pretreatment . However, certain pretreatment techniques such as those involving ionic liquids are known to completely destroy the crystalline cellulose structure .…”
Section: Resultsmentioning
confidence: 99%
“…The process of producing glucose from rice straw was referred to the method of our previous study with some modifications [34]. Briefly, approximately 15 g of RS powder was extracted with absolute ethanol by the Soxhlet extraction method for 24 h and vacuum dried to obtain the extract-free RS.…”
Section: Process For Producing Glucose From Rice Strawmentioning
confidence: 99%
“…In the previous study, a combined process of liquid hot water (LHW) and phosphotungstic acid (PTA) pretreatment and enzymatic hydrolysis was used to produce fermentable sugars from rice straw [34]. The glucose yield was about 27.6% by the mass of air-dried straw.…”
Section: Introductionmentioning
confidence: 99%